Empowering Posyandu Cadres: Psychoeducation on the Psychological Role of Parents in Preventing Childhood Stunting - Nilna Muna; Nuke Aulia Pratiwi; Qomarullah Agustiya Jannah; Risalatul Ummah; Sultan Fadillah Ardiansyah; Uyunun Nadhira Rahma Yulianti; Lucky Abrorry; Zuardin Zuardin; Nailatin Fauziyah (Jurnal Empathy Pengabdian Kepada Masyarakat, 2026)
Background: Stunting affects approximately 149 million children globally, with Indonesia reporting 24% prevalence in 2022. Inappropriate parenting practices and parental psychological factors significantly contribute to stunting. This community service aimed to enhance community knowledge about the psychological role of parents in stunting prevention through psychoeducation intervention. Methods: Participatory Action Research (PAR) method was employed involving 20 posyandu cadres from Pagesangan sub-district, Surabaya. The intervention consisted of a 90-minute psychoeducation session, accompanied by leaflet distribution. The research stages included intake process, assessment, psychoeducation implementation, and evaluation. Pre-test and post-test assessments were administered verbally to measure knowledge changes. Results: Significant knowledge improvement was observed. Pre-test showed 85% of participants understood stunting only as malnutrition, while post-test revealed 100% could comprehensively explain stunting as multifaceted growth failure. All participants (100%) demonstrated improved understanding of psychological factors including psychosocial stimulation, parenting practices, and maternal mental health. Knowledge about stunting risks increased substantially, with all participants identifying cognitive, motor, and verbal developmental impairments. Follow-up assessment indicated 93% of participants disseminated information to their communities and 80% implemented preventive measures in posyandu activities. Conclusion: Psychoeducation effectively increased community knowledge about parental psychological aspects in stunting prevention. This community-based approach can be implemented to reduce stunting rates through empowering posyandu cadres as health information disseminators.